2021
DOI: 10.1097/lbr.0000000000000821
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Novel, Shortened, Indwelling Pleural Catheter (PleurX) for the Ambulatory Management of Malignant Pleural Effusion

Abstract: Background: Indwelling pleural catheters are frequently used for the treatment of malignant pleural effusion. The PleurX catheter (Becton, Dickinson and Company) is a commonly used indwelling pleural catheter across Canada. The traditional PleurX catheter is designed with a long segment of tubing outside of the patient’s chest, making insertion, drainage, and dressing changes awkward. Our clinic developed a novel, shortened, PleurX catheter that is easier to handle. Methods: We conducted retrospective chart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…As shown in Figure 1, 7486 relevant studies were initially identified, among which 82 were retained for further evaluation. We ultimately included 41 studies published between 1999 and 2021 15–55 . Table 1 shows basic study information and the results of the quality evaluations of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1, 7486 relevant studies were initially identified, among which 82 were retained for further evaluation. We ultimately included 41 studies published between 1999 and 2021 15–55 . Table 1 shows basic study information and the results of the quality evaluations of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…We ultimately included 41 studies published between 1999 and 2021. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 Table 1 shows basic study information and the results of the quality evaluations of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, they noted that a majority of nurses preferred the shorter catheter. 3 Three respondents (11%) preferred the longer catheter, 20 respondents (74%) preferred the shorter catheter, and 4 respondents (15%) had no preference. The most cited reasons for a preference for the shorter catheter included easier catheter manipulation (7 respondents), easier dressing changes (11 respondents), perceived improvements in patient comfort (5 respondents), and easier maintenance of sterility (4 respondents).…”
mentioning
confidence: 97%
“…The most cited reasons for a preference for the shorter catheter included easier catheter manipulation (7 respondents), easier dressing changes (11 respondents), perceived improvements in patient comfort (5 respondents), and easier maintenance of sterility (4 respondents). Respondents who preferred the longer catheter cited easier catheter manipulation with the longer catheter (2 respondents) 3…”
mentioning
confidence: 99%
See 1 more Smart Citation